Reversal of multidrug resistance in drug-resistant human gastric cancer cell line SGC7901/VCR by antiprogestin drug mifepristone - Li, Da-Qiang (World J Gastroenterol, 2004)
AIM: To explore the reversal effect of mifepristone on multidrug resistance (MDR) in drug-resistant human gastric cancer cell line SGC7901/VCR and its mechanisms. METHODS: Expression of multidrug resistance-associated protein (MRP) was detected using reverse transcription-polymerase chain reaction (RT-PCR). Flow cytometry was used to assay the expression of P-glycoprotein (P-gp), Bcl-2, Bax, and the mean fluorescent intensity of intracellular rhodamine 123 in the cells. Meanwhile, the protein levels of Bcl-2 and Bax were also detected by Western blotting analysis. The sensitivity of cells to the anticancer agent, vincrimycin (VCR), and the intracellular [(3)H]VCR accumulation were determined by tetrazolium blue (MTT) assay and a liquid scintillation counter, respectively. RESULTS: Expression of MRP and P-gp in SGC7901/VCR cells was 6.04-and 8.37-fold higher as compared with its parental SGC7901 cells, respectively. After treatment with 1, 5, 10, and 20 μmol/L mifepristone, SGC7901/VCR cells showed a 1.34-, 2.29-, 3.11-, and 3.71-fold increase in the accumulation of intracellular VCR, a known substrate of MRP, and a 1.03-, 2.04-, 3.08-, and 3.68-fold increase in the retention of rhodamine 123, an indicator of P-gp function, respectively. MTT assay revealed that the resistance of SGC7901/VCR cells to VCR was 11.96-fold higher than that of its parental cells. The chemosensitivity of SGC7901/VCR cells to VCR was enhanced by 1.02-, 7.19-, 12.84-, and 21.17-fold after treatment with mifepristone at above-mentioned dose. After 96 h of incubation with mifepristone 10 μmol/L, a concentration close to plasma concentrations achievable in human, the expression of Bcl-2 protein was decreased to (9.21 ± 0.65)% from (25.32 ± 1.44)%, whereas the expression of Bax protein was increased to (19.69 ± 1.13)% from (1.24 ± 0.78)% (P < 0.01). Additionally, the effects of mifepristone on the expression of Bcl-2 and Bax proteins in SGC7901/VCR cells were further demonstrated by Western blotting analysis. CONCLUSION: Mifepristone has potent reversal effect on MDR in SGC7901/VCR via inhibiting the function of MRP and P-gp, modulating the expression of Bcl-2 and Bax proteins, and enhancing the sensitivity to anticancer agent VCR.